2011
DOI: 10.1063/1.3582244
|View full text |Cite
|
Sign up to set email alerts
|

Structural controlled magnetic anisotropy in Heusler L1−MnGa epitaxial thin films

Abstract: Epitaxial structure and magnetic anisotropies of metastable single crystal Co 0.70 Mn 0.30 film

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
25
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(26 citation statements)
references
References 15 publications
1
25
0
Order By: Relevance
“…It was found that the crystalline orientation of the Ferromagnetic L1 0 -MnGa thin films, which epitaxially grown on GaN, sapphire, and MgO substrates, differ due to the influence of the substrate [32]. The in-plane and out-of-plane anisotropy is directly determined by the crystal orientation of the film and could be controlled via selection of the substrates.…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…It was found that the crystalline orientation of the Ferromagnetic L1 0 -MnGa thin films, which epitaxially grown on GaN, sapphire, and MgO substrates, differ due to the influence of the substrate [32]. The in-plane and out-of-plane anisotropy is directly determined by the crystal orientation of the film and could be controlled via selection of the substrates.…”
Section: Introductionmentioning
confidence: 97%
“…Previous experimental results have shown that the Mn-Ga alloys grown on substrate or in superlattices have affected the tetragonality of the crystal structures, which is attributed to the lattice strain, and this has influence on the magnetic properties and the magnetocrystalline anisotropy of the alloys [18,[30][31][32][33][34][35][36]. It was found that the crystalline orientation of the Ferromagnetic L1 0 -MnGa thin films, which epitaxially grown on GaN, sapphire, and MgO substrates, differ due to the influence of the substrate [32].…”
Section: Introductionmentioning
confidence: 99%
“…An excellent candidate for satisfying these properties is MnGa alloys [2,3]. The structural, magnetic, and transport properties as well as spin polarization and magnetization dynamics of MnGa with PMA have been investigated in previous studies [4][5][6][7][8][9]. The new challenge concerning to MnGa alloys is increasing the tunnel magnetoresistance (TMR) ratio based on MgOMTJs.…”
Section: Introductionmentioning
confidence: 98%
“…The reported coercivities of L1 0 -MnGa films and powders are in the range of 2.2-6.2 kOe, which is not sufficiently high to qualify as a candidate for rare-earth-free magnets. [6][7][8][9][10][11] The D0 22 -Mn 3 Ga intermetallic compound, known as the Al 3 Ti-type MnGa phase, also has a tetragonal structure (I4/mmm). 12 Three different Mn 3 Ga intermetallic compounds are known to exits: the tetragonal D0 22 -Mn 3 Ga intermetallic compound, hexagonal D0 19 -Mn 3 Ga intermetallic compound, and cubic L2 1 -Mn 3 Ga intermetallic compound.…”
Section: Introductionmentioning
confidence: 99%